2013
DOI: 10.1680/ener.12.00010
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive sensors for offshore scour monitoring

Abstract: One of the main challenges in the design and operation of offshore wind turbines arises from the uncertainty about maximum scour depth around their foundations. Scour action can lead to excessive excavation of the surrounding seabed and is being considered as a major risk for offshore wind farm developments. An ability to gather information concerning the evolution of scouring will enable the validation of models derived from laboratory-based studies, the assessment of different engineering designs and the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Michalis et al [80] proposed a similar solution, but with no moving parts. A probe with sensors distributed along its length is embedded into the seabed.…”
Section: Existing Systemsmentioning
confidence: 99%
“…Michalis et al [80] proposed a similar solution, but with no moving parts. A probe with sensors distributed along its length is embedded into the seabed.…”
Section: Existing Systemsmentioning
confidence: 99%
“…The response of the ADR probe and the calibration curve scaling the electrical signal to Preliminary experiments revealed temperature and salinity effects on the signals of a sensor that was embedded into various sediment types [24,25]. Consequently, another set of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 The temperature influence on the response of the submerged sensor was also evaluated and …”
Section: Sensor Calibration and Sensitivity To Water Salinity And Temmentioning
confidence: 99%
“…Furthermore, a study applied 3D computational fluid dynamics (CFD) to develop a numerical model to examine the seabed boundary-layer flow around monopile and hexagonal gravity-based foundations of offshore wind turbines; the flow was examined to determine the formation of horseshoe vortices and flow structures to estimate potential scour for engineering designs. The results showed that the horseshoe vortex size for the hexagonal gravity-based foundation was smaller than that for the monopile foundation [26][27][28][29][30]. Another study also proposed a wireless network monitoring system connected to an array of small capacitive sensor probes installed around a foundation for observing scour and sediment deposition processes; this system is similar to a sonar scanning approach [31].…”
Section: Introductionmentioning
confidence: 99%